Film and Ethics: Foreclosed Encounters - Kokalov, Assen (Imagofagia, 2021)
Sobre Downing, Lisa y Libby Saxton. Film and Ethics: Foreclosed Encounters. London, Routledge, 2010, 160 pp., ISBN:978-0-415-40927R. Palabras clave: reseña, Lisa Downning, Libby Saxton, Film and Ethics: Foreclosed Encounters.